Impact of Integrated Postharvest Management and Extension Education on Yam Storage Efficiency Among Omambala Farmers: A Study on Heteroligus Meles (Yam beetle) - Okeke Tobechukwu Ebele (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2025)
Yam farming is an essential agricultural practice in Nigeria, particularly in rural communities like Omambala, where it serves as a major source of livelihood and food security. However, farmers face significant challenges during the postharvest phase, with pests such as Heteroligus Meles (yam beetle) causing considerable damage to stored yams. The study adopted a descriptive survey design and was conducted in Anambra East Local Government Area, a major yam-producing region in Anambra State. The target population included medium- to large-scale yam farmers and agricultural professionals. A purposive sample of 94 respondents was selected. Data were collected using a structured questionnaire, validated by experts, and tested for reliability (Cronbach’s alpha = 0.8). Descriptive and inferential statistics, including Univariate Analysis of Variance, were used for data analysis at the 0.05 significance level. The findings revealed that integrated postharvest management significantly reduced infestation and postharvest losses caused by Heteroligus meles. Farmers who applied improved techniques recorded better storage outcomes. Moreover, the study found that regular extension education enhanced farmers’ awareness and practical skills in pest control, leading to more effective implementation of protective measures. Farmer awareness was positively correlated with the use of recommended storage practices and pest management solutions. The study concludes that combining integrated postharvest strategies with targeted extension education and awareness programs can greatly improve yam storage efficiency and reduce pest-related losses. It recommends the strengthening of extension services and the promotion of farmer-friendly pest control technologies to ensure sustainable yam production and food security in the region.